Implementasi Inovasi Metode Reward dan Punishment dalam Menegakkan Kedisiplinan Berbahasa Santri Pondok Modern Ar-Risalah Ponorogo - Sujatmiko, M.; Muji Lestari, Titis Wahyu (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Initial observations indicate that approximately 68% of students tend to use non-formal language outside of instructional activities, especially when interacting with their peers. This condition is related to the students’ low internal motivation to use foreign languages and the strong influence of a social environment that supports the use of their mother tongue. In this context, the reward and punishment method has become one of the strategies widely applied by educational institutions to enforce discipline, as it has been proven to motivate learners to achieve and behave positively. At Pondok Modern Ar-Risalah Ponorogo, this method is employed to enforce language discipline through various innovative practices. This study aims to investigate these forms of innovation in order to enhance students’ language discipline. This research adopts a descriptive qualitative approach using observation, interviews, and documentation. The findings reveal several innovations in the implementation of reward and punishment, including rewards in the form of gifts, praise, and entertainment, as well as punishments such as memorizing vocabulary, writing stories in Arabic or English, and wearing a special vest as a reminder of discipline. These innovations have proven effective in improving students’ language discipline, and activities such as muhadorah, muhadasah, drama competitions, and speech contests further strengthen a language-rich environment that supports the continuous development of students’ language skills.